Backward Running: Acute Effects on Sprint Performance in Preadolescent Boys - Dimitrios Petrakis; Eleni Bassa; Anastasia Papavasileiou; Anthi Xenofondos; Dimitrios A. Patikas (Sports, 2020)
The aim of this study was to examine the acute effect of backward running (BwR) during warm-up on a 20-m sprint of boys’ performance, compared to forward running (FwR). Fourteen recreationally active preadolescent boys (aged 12.5 ± 0.5 years) were examined in 3 protocols: warm-up (control condition), warm-up with 3 × 10 m additional BwR sprints and warm-up with 3 × 10 m additional FwR sprints. Participants were evaluated 4 minutes after each protocol on a 20-m sprint and intermediate distances, as well as the rate of perceived exertion (RPE). Sprint speed across 10-20 m was significantly higher for the BwR warm-up compared to the regular warm-up (p < 0.05) and a significantly higher RPE after the BwR and FwR protocols compared to the control condition was recorded (p < 0.05). No significant difference was detected across the distances 0–5, 5–10, 0–10 and 0–20 m. Although adding 3 × 10-m sprints of BwR or FwR after the warm-up did not enhance performance in a 20 m sprint of preadolescent boys, the positive effect of BwR across 10–20 m distance suggests that BwR could be an alternative means for enhancing performance for certain phases of a sprint for this age. However, preadolescent boys’ response to different sprint conditioning exercise stimuli and the optimization of rest time to maximize performance remain to be determined.